2021
DOI: 10.1101/2021.12.17.473165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The acquisition of clinically relevant amoxicillin resistance in Streptococcus pneumoniae requires ordered horizontal gene transfer of four loci

Abstract: Understanding how antimicrobial resistance spreads is critical for optimal application of new treatments. In the naturally competent human pathogen Streptococcus pneumoniae, resistance to β-lactam antibiotics is mediated by recombination events in genes encoding the target proteins, resulting in reduced drug binding affinity. However, for the front-line antibiotic amoxicillin, the exact mechanism of resistance still needs to be elucidated. Through successive rounds of transformation with genomic DNA from a cli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 122 publications
(225 reference statements)
0
1
0
Order By: Relevance
“…In S. pneumoniae , resistance toward β-lactam antibiotics is mostly caused by mosaic PBPs. These resistance-conferring mosaic PBPs are formed by recombination events following horizontal gene transfer from β-lactam resistant donor strains ( Jensen et al, 2015 ; Hakenbeck et al, 2012 ; Gibson et al, 2021 ). It has been shown that many resistance-conferring PBP mutations are associated with considerable fitness costs that need to be compensated for ( Albarracín Orio et al, 2011 ; Zerfass et al, 2009 ; Smith and Klugman, 2001 ) and that mosaic PBPs significantly alter the cell wall structure, potentially by a decrease in affinity for their natural substrate ( Garcia-Bustos and Tomasz, 1990 ).…”
Section: Discussionmentioning
confidence: 99%
“…In S. pneumoniae , resistance toward β-lactam antibiotics is mostly caused by mosaic PBPs. These resistance-conferring mosaic PBPs are formed by recombination events following horizontal gene transfer from β-lactam resistant donor strains ( Jensen et al, 2015 ; Hakenbeck et al, 2012 ; Gibson et al, 2021 ). It has been shown that many resistance-conferring PBP mutations are associated with considerable fitness costs that need to be compensated for ( Albarracín Orio et al, 2011 ; Zerfass et al, 2009 ; Smith and Klugman, 2001 ) and that mosaic PBPs significantly alter the cell wall structure, potentially by a decrease in affinity for their natural substrate ( Garcia-Bustos and Tomasz, 1990 ).…”
Section: Discussionmentioning
confidence: 99%